Spermatogenic cell-specific SPACA4 is essential for efficient sperm-zona pellucida binding in vitro - Chen, Lin; Song, Junli; Zhang, Jinglei; Luo, Zicong; Chen, Xuren; Zhou, Canquan; Shen, Xiaoting (Frontiers in Cell and Developmental Biology, 2023)
Fertilization is a complex and highly regulated process that involves a series of molecular interactions between sperm and eggs. However, the mechanisms of proteins involved in human fertilization, such as that of testis-specific SPACA4, remain poorly understood. Here, we demonstrated that SPACA4 is a spermatogenic cell-specific protein. SPACA4 is expressed during spermatogenesis, upregulated in early stage spermatids, and downregulated in elongating spermatids., SPACA4 is located in the anterior head plasma membrane of the sperm in addition to the acrosome and is lost during the acrosome reaction. Incubation with antibodies against SPACA4 inhibited the binding of spermatozoa to zona pellucida. SPACA4 protein expression levels across different semen parameters were similar, but varied significantly among patients. A prospective clinical study found no association between SPACA4 protein levels and fertilization or cleavage rates. Thus, the study suggests a novel function for SPACA4 in human fertilization in a non-dose-dependent manner. However, a larger clinical trial is required to evaluate the potential use of sperm SPACA4 protein levels to predict fertilization potential.